Duty to Accommodate - Hatfield, Robert (Just Labour, 2005)
Workers traditionally accommodated co-workers. But, as accommodation law developed, tensions emerged. In Meiorin: accommodation is the norm. Employers must eliminate standards, rules, practices, etc. that discriminate on prohibited grounds, up to undue hardship. In the Canadian Human Rights Act, undue hardship includes only cost, health and safety. Other jurisdictions, following Central Alberta Dairy Pool, consider: impact on the collective agreement, other workers’ rights, employee morale, size of operation, workforce and facility adaptability. O’Malley clarifies adverse affect discrimination. A rule, although made in good faith, may discriminate “if it affects a person … differently from others”. Accommodation may override contract provisions (Renaud), including seniority (Goyette). While employers have principal responsibility for accommodation, unions have a role too (Gohm). Unions reduce accommodation tensions by: auditing collective agreements, reviewing accommodation procedures, educating members and leaders.